Greed that Occurs in Kingdom of the Planet of the Apes Movie - Tita Keisya Amanda; Putri Wulandari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
The purpose of this study is to analyze the portrayal of greed and power in the film Planet of the Apes and focus on how these themes affect the relationship between humans and apes. This study will focus on understanding the role of greed and power in social and interspecies dynamics and explore how these destructive forces shape character behavior as well as the broader conflict in the story. This study uses qualitative descriptive analysis to explore the themes of "greed" and "power" in Planet of the Apes. The study employs descriptive research to explore how these themes are intertwined in the plot, particularly the dynamics between humans and apes. The study emphasizes the destructive effects of greed, which leads to conflict, exploitation, and oppression and affects both species. Proximus symbolizes the greed of apes, who misuse Caesar's teachings to fuel their violent ambitions, while Mai symbolizes the greed of humans, who crave manipulation and control. The results of this study show how humans struggle to coexist with the greedy apes, thus reinforcing the narrative of inevitable conflict and power struggle.